Resistance of engine oil treated wood to termite attack (2010)
Wood samples of Ceiba pentandra, Antiaris toxicaria and Triplochiton scleroxylon were treated with new and spent engine oils using three treatments methods; brushing, soaking for 24 hours and soaking for 48 hours. The treated wood samples and control were exposed to Termite attack for 16 weeks using graveyard method. Visual assessment and percentage weight loss were employed to evaluate the effects of the preservative engine oil. Data collected were subjected to analysis of variance (ANOVA) at 0.05 probability level. The average weight loss for Ceiba pentandra, Antiaris toxicaria and Triplochiton scleroxylon ranged between 0.64-1.94%. 0.48-1.47% and 0.38-1.32% respectively. Wood samples treated using brush recorded highest weight loss for the three species and the two types of engine oil. Results of the statistical analysis (p< 0.05) showed that only the method of preservative application has significant effect on the weight loss per treatment combination while the type of engine oil spent and wood species are not statistically different. Prolonged soaking of wood in spent engine oil however gave a better result compared to new engine oil. Thus spent engine oil has potentials for wood preservation.